Metropolitan government under martial law the Metro Manila commission experiment - Ruland, Jurgen (Philippine Journal of Public Administration, 1985)
The pattern of service delivery in metropolitan Manila did not significantly improve despite the reorganization of the metropolitan local governments with the creation of a Metro Manila Commission (MMC). Although the MMC experiment was designed to control rapid urbanization and un-restrained growth in the Metropolitan Manila Area (MMA), it was actually part of successive political maneuvers to stabilize and consolidate the Marcos regime. The reorganization in effect centralized metropolitan governance through the Ministry of Human Settlements and at the same time severely curtailed the power of local governments. As long as metropolitan governance continues to be a direct part in the national power game, there will be no substantial change in the pattern of service delivery and living conditions in the MMA.